Romanticism and the re-Invention of modern religion : the reconciliation of German Idealism and platonic realism - Hampton, Alexander J. B. (Cambridge University Press, 2019)
Examines how early German Romanticism combined post-Kantian idealism and Platonic-Christian realism to develop a new aesthetics of religion.